2017
DOI: 10.1080/23279095.2017.1341410
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced detection of feigned cognitive impairment using per item response time measurements in the Word Memory Test

Abstract: Response time (RT) is a less obvious outcome measure than conventional accuracy measures used in performance validity tests (PVTs). It is also under less conscious control and is affected by cognitive processes associated with deception. Studies that assessed the utility of RT for the detection of feigned cognitive impairment are however numbered. Moreover, RT variability was not assessed in a clinically used PVT. In the current study, we assessed the utility of RT measures for the detection of feigned cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…Next, the regression model was used to compute a scale (termed MOXO-d-CPT feigned ADHD scale or combined scale ), which combined the unique contribution of each of the individual indices. The equation’s outcome, P(simulators), estimates the probability (range = 0-1) of a participant being classified as a simulator, given the participant’s scores in the indices (see Lupu et al, 2018). See Table 1 for the logistic regression analysis and the combined scale’s equation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the regression model was used to compute a scale (termed MOXO-d-CPT feigned ADHD scale or combined scale ), which combined the unique contribution of each of the individual indices. The equation’s outcome, P(simulators), estimates the probability (range = 0-1) of a participant being classified as a simulator, given the participant’s scores in the indices (see Lupu et al, 2018). See Table 1 for the logistic regression analysis and the combined scale’s equation.…”
Section: Resultsmentioning
confidence: 99%
“…This is a well-established verbal forced-choice recognition PVT (Green, 2003). It is widely used in both clinical (Martin, Schroeder, & Odland, 2015; Schroeder, Martin, & Odland, 2016) and research settings (e.g., Bryant et al, 2018; Lupu, Elbaum, Wagner, & Braw, 2018) and was found to have high sensitivity and adequate specificity in a variety of neurological conditions (Greve, Curtis, & Bianchini, 2013). The immediate recognition (IR)-score and delayed recognition (DR)-score (% correct responses in the IR and DR subtests, respectively), as well as the consistency score (CNS), were used to classify participants according to the WMT’s classification scheme (Green, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…In PVT research, a number of other studies have investigated both reaction time parameters (e.g., Stevens & Merten, 2010;Willison & Tombaugh, 2006) and response times in neuropsychological tests (e.g., Patrick et al, 2021), freestanding validity tests (e.g., Jansen et al, 2020;Kanser et al, 2019;Lupu et al, 2018), and computerized questionnaires (e.g., Cerny et al, 2021). Several studies investigated performance validity using continuous performance tests, such as the Test of Variables of Attention (T.O.V.A., Leark et al, 2008;e.g., recently, Harrison & Armstrong, 2020;Pollock et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the TAP Alertness subtest, this test is much more time-consuming and has a component of monotony. The common denominator of most studies is the assumption that reaction and response times are under lower conscious control and, therefore, may be harder to manipulate, and such manipulations might be more difficult to coach (Lupu et al, 2018;Vagnini et al, 2008). It also relates to studies in other fields of deception detection where manipulations in response behavior led to elevated reaction times (Lukács et al, 2021;Suchotzki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, PVTs are typically used to predict insufficient engagement on separate, non-PVT measures, occasionally leading to challenging discrepancies (Loring & Goldstein, 2019) or false positives (Lippa, 2018). In addition, PVTs usually do not factor in speed of responding, though using speed in addition to accuracy may increase the sensitivity of PVTs (Kanser, Rapport, Bashem, & Hanks, 2019;Lupu, Elbaum, Wagner, & Braw, 2018). Innovative methods for performance validity that leverage modern psychometric modeling would be especially beneficial for acquisition of large samples over the internet or for tests administered through telehealth.…”
Section: Development and Application Of Novel Performance Validity Metrics For Computerized Neurocognitive Batteriesmentioning
confidence: 99%